Analisis Etika Bisnis Islam dalam Kinerja Pedagang Bakso Mercon Pak Fadelun di Bangkalan - Zumrotul Latifah; Abdur Rohman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In the process of increasing the growth of the business they run, MSME actors will certainly encounter obstacles. To start and run a business certainly cannot be separated from ethics, because implementing ethics in business will direct human life to achieve worldly happiness in the form of obtaining material benefits and afterlife happiness by obtaining the pleasure of Allah. The reality that exists now has occurred a shift in sharia business, for example, many business people are involved in usury transactions, dishonest, reducing scales or doses, gharar, fraud, hoarding, scandals, corruption, collusion, and ijon. This shows that the sharia business that is carried out still cannot be applied among the community so that there is unhealthy competition among business people. With this, the researcher wants to know whether one of the Muslim meatball traders living in Bangkalan Regency with the majority of his business customers being Muslims applies Islamic business ethics as the basis for his business activities. This research method uses descriptive qualitative analysis method because this research aims to explain the application of Islamic business ethics. This research method is a field research method conducted in Bangkalan District, Bangkalan Regency. Collecting data in the study using several techniques, namely: Observation, and Interview. The results of this study explain that Mr. Fadelun's meatballs have applied the principles of Islamic business ethics, namely: (1) Principle of Unity (2) Principle of Justice (3) Principle of Free Will (4) Principle of Responsibility (5) principle of truth.